2016
DOI: 10.3399/bjgp16x686101
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of care in primary care and association with survival in older people: a 17-year prospective cohort study

Abstract: BackgroundAlthough continuity of care is a widely accepted core principle of primary care, the evidence about its benefits is still weak. AimTo investigate whether continuity of care in general practice is associated with better survival in older people. Design and settingData were derived from the Longitudinal Aging Study Amsterdam, an ongoing cohort study in older people in the Netherlands. The study sample consisted of 1712 older adults aged ≥60 years, with 3-year follow-up cycles up to 17 years (1992)(1993… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 48 publications
7
103
0
Order By: Relevance
“…Direct comparison with other studies of the association between consultation frequency in general practice and mortality is not possible due to the absence of similar studies. Nevertheless, studies measuring continuity of care have reported an association between higher continuity of care in primary care and lower mortality . In line with our findings, Wolinsky et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Direct comparison with other studies of the association between consultation frequency in general practice and mortality is not possible due to the absence of similar studies. Nevertheless, studies measuring continuity of care have reported an association between higher continuity of care in primary care and lower mortality . In line with our findings, Wolinsky et al .…”
Section: Discussionsupporting
confidence: 92%
“…Patients with low GP consultation frequency are known to have a higher mortality . Our findings added new knowledge on the association between usual GP consultation frequency and advanced cancer stage at diagnosis.…”
Section: Discussionmentioning
confidence: 54%
“…36 As our study shows, older adults who experienced marked discontinuity of care had an increased risk of emergency hospital admission. This finding might be highly relevant for policy makers because of increasing size of elderly populations.…”
Section: Implications For General Practices and Future Researchmentioning
confidence: 64%
“…Self‐esteem includes individuals’ self‐perceptions and feelings about themselves (Ryan & Brown, ), as well as the image they have of their own characteristics and skills in relation to themselves and others (Baumeister, Campbell, & Vohs, ). Mastery relates to the degree to which people perceive themselves as having influence and control over their circumstances and significant events in their lives (Ben‐Zur, ; Pearlin & Lieberman, ), as opposed to being governed, for example, by chance or the needs and demands of others (Maarsingh, Henry, van de Ven, & Deeg, ). A sense of mastery is achieved when individuals believe that they are able to shape and influence their physical, social, and behavioral reality to suit their own perceptions and desires (Ben‐Zur, ).…”
Section: Introductionmentioning
confidence: 99%